Apoptotic abnormalities in differential gene expression in peripheral blood mononuclear cells from children with Fabry disease - Moore, David F.; Ries, Markus (Acta paediatrica, 2008)
Aim: This study was designed to examine the effect of enzyme replacement therapy (ERT) on differential gene expression in peripheral blood mononuclear cells (PBMCs) of children with Fabry disease who had not previously been exposed to ERT. Methods: Thirteen children with Fabry disease (age range, 6.5-17.0 years) were studied as part of a 6-month, open-label study of ERT with agalsidase alfa. Paired blood samples were taken at the start of the study and after 6 months of ERT. Further blood samples were also taken from 16 age-matched control subjects. PBMCs were isolated and, following RNA extraction, differential gene expression analysis was performed using the Human Genome U133 Plus 2.0 microarray. Results: Twenty-one genes were determined to be differentially expressed in PBMCs of ERT-naïve children with Fabry disease compared with healthy controls; neuronal apoptosis inhibitory protein ranked as the most significantly differentially expressed gene. Comparison of gene expression in children with Fabry disease prior to and after ERT showed that two genes were significantly differentially expressed (p ≤ 0.05) following treatment; the expressed sequence tag (probe set ID, 243259_at) was downregulated, while expression of apoptosis-inducing factor was increased, possibly as an antioxidant counter-regulatory response. Conclusion: This study identifies a number of genes that are differentially expressed in a small cohort of children with Fabry disease relative to healthy controls. These genes may relate to the underlying biological abnormalities in Fabry disease.
Gesehen am 09.05.2019